On the ro-vibrational energies for the lithium dimer; maximum-possible rotational levels - Mustafa, Omar (IOP Publishing, 2015)
The Deng-Fan potential is used to discuss the reliability of the improved Greene-Aldrich approximation and the factorization recipe of Badawi et al [17] for the central attractive/ repulsive core J( J + 1)/2 mu r(2). The factorization recipe is shown to be a more reliable approximation and is used to obtain the rotational-vibrational energies for the a(3)Sigma(+)(u)-Li-7(2) dimer. For each vibrational state only a limited number of the rotational levels are found to be supported by the a(3)Sigma(+)(u)-Li-7(2) dimer.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication
Keywords: ASIGMA(+)(U) STATE, lithium dimer; LI-7, DIATOMIC-MOLECULES, SPECTROSCOPY; OSCILLATOR, PHYSICS, ATOMIC; MOLECULAR & CHEMICAL, maximum-possible rotational levels, OPTICS; ro-vibrational energies, CURVE, lithium dimmer; Quantum Physics, Chemical Physics, Physics